2021
DOI: 10.3389/fphys.2021.775750
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wearing Surgical Face Masks During Exercise: Does Intensity Matter?

Abstract: Face masks are widely recommended as means of controlling the coronavirus disease outbreak. This study aimed to examine the physiological and perceptual responses of wearing surgical face masks while exercising at different intensities. Thirteen healthy young adults (mean age, 21.9 ± 1.4 years) conducted randomized crossover trials with or without a surgical face mask. In each trial, participants completed an incremental treadmill protocol, with three 6-min stages (light, moderate, and vigorous at 25, 50, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 23 publications
6
20
0
1
Order By: Relevance
“…Although RPE at point of exhaustion was unaffected by mask use, the dyspnoea ratings were higher and the authors hypothesized that discomfort from mask wearing led to reduced exercise performance. This was also observed in studies by Fikenzer et al (2020) , Egger et al (2022) and Poon et al (2021) .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although RPE at point of exhaustion was unaffected by mask use, the dyspnoea ratings were higher and the authors hypothesized that discomfort from mask wearing led to reduced exercise performance. This was also observed in studies by Fikenzer et al (2020) , Egger et al (2022) and Poon et al (2021) .…”
Section: Discussionsupporting
confidence: 83%
“…Alongside the conflicting data, there were also key differences in study conduct, with earlier studies employing the use of a face mask worn together with a spirometry mask. Poon et al (2021) conducted a crossover trial of 13 individuals that found no significant differences in physiological outcomes during exercise with the use of a face mask, although an increased rate of perceived exertion was reported with mask use on vigorous exertion. Fischer et al (2022) , conducted a similar trial in a population including those with coronary artery disease or hypertension, and concluded that face mask use during exercise reduced peak power output without differences in hemodynamic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, pandemic restrictions could have mainly limited opportunities for practicing the vigorous physical activity required for muscular stimulation but less constrained opportunities for developing moderate physical activity that would allow partially preserving cardiorespiratory fitness. On the other hand, it must be pointed out that during the pandemic year, the 20 m SRT was performed while students wore face masks, and therefore, these results would support the lack of influence of this condition on maximum cardiorespiratory performance [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Rosa et al (2021) revealed that wearing an FFP2 or N95 face mask significantly increased the rating of perceived exertion during moderate-resistance exercise (four sets of bench press until movement failure at 50% one-RM) [ 11 ]. Another study reported that wearing an SM increased the rating of perceived exertion only when the intensity reached a high level (75% maximal oxygen uptake) and caused more discomfort in terms of heat, humidity, and breathing resistance [ 41 ]. In addition, the use of an SM or FFP2/N95 mask led to increased discomfort in terms of breathing resistance, tightness, feeling unfit, heat, fatigue, itchiness, and overall discomfort [ 5 ].…”
Section: Discussionmentioning
confidence: 99%